Teachers’ Experience on the Contributions of Formative Assessment in Students’ Learning - Bhandari, Bhim Lal; Kshetree, Arun Kumar (Kalika Journal of Multidisciplinary Research, 2024)
Assessment is one of the significant and inherent parts of teaching to improve the entire teaching-learning activities. It is also an essential component of language teaching which provides feedback to teachers and learners. This paper aims to explore teachers’ experiences with the contributions of formative assessment in students’ learning and the problems that they face in implementing it. To accomplish the objectives, we used the narrative inquiry research approach. To capture the participants' life experiences of FA, four English instructors from four community schools in Rupandehi were purposively chosen as research participants. We employed semi-structured interviews to gather information from them. This study explores that formative assessment significantly contributes to students’ success by motivating them, identifying their weaknesses, and fostering continuous improvement. It enhances teacher effectiveness by providing insights into student progress, enabling adjustments to teaching strategies. FA offers constructive feedback that benefits both students and teachers, improving classroom activities and promoting self-directed learning. Various FA methods, such as group work and assignments, positively contribute to academic performance. However, challenges like curriculum overload, time constraints, and insufficient support hinder its full implementation. The implications of this study can offer insights to policy makers, students and teachers in the efficiency of using FA practices exploring their inadequacies and focusing on areas that require more attention and work.